RANSPLANTING DATES AND NITROGEN LEVELS INFLUENCES ON GROWTH, YIELD ATTRIBUTES, AND YIELD OF SUMMER PEARL MILLET - M. CHOUHAN; N. N. GUDADHE; DINESH KUMAR; A. K. KUMAWAT; R. KUMAR (The Bioscan, 2015)
The experiment was taken with three dates of transplanting viz, Normal drilling at RSD (T1), first transplanting (Transplanting on RSD, T2) and second transplanting (Transplanting 25 days after RSD, T3) and four levels of nitrogen viz., 75% RDN (N1), 75% RDN + Azospirillum (N2), 100% RDN (N3), and 125% RDN (N4). Treatment T1 recorded significantly higher plant height (178.69 cm) length of earhead (21.79 cm), girth of earhead (9.71 cm), test weight (9.01 g), grain yield (35.90 kg ha-1) and straw yield (92.11 kg ha-1), and found statistically at par with treatment T2. Among nitrogen levels Significantly higher length of earhead (22.25 cm), girth of earhead (9.79 cm), test weight (9.10 g), grain yield (37.93 kg ha-1) and straw yield (94.45 kg ha-1) were recorded under treatment N4 but in case of length of earhead and grain yield, treatment N4 did not differ significantly with N3. Hence, summer pearlmillet crop should be sown by normal drilling or transplanting on RSD with 100% RDN.